A 3D thermal model of SynRM with segmented rotor considering anisotropic conductivity - Mohd Azri Hizami, Rasid; Ospina, Alejandro; Benkara, Khadija El Kadri; Lanfranchi, Vincent (IEE, 2021)
This paper presents a lumped-parameter thermal network (LPTN) model construction of a synchronous reluctance machine (SynRM) with a segmented rotor and its validation. The 180W machine is intended to actuate an automotive clutch thus, installed at an ambient temperature up to 140◦C. In such a machine, to make sure that a precise prediction of the temperature inside the machine can be achieved, the deduction of thermal resistance of the anisotropic component, surface contact, and external casing convection need particular attention. The external casing convection has been experimentally identified. The contact resistance between components was computed using an effective air gap. The method used to compute thermal resistances of anisotropic components and surface contact is explained. The identification method used to deduce the thermal resistance of the external surface is also presented. Finally, validation experiments at different operating points of copper losses have shown that the 3D LPTN model is precise and robust with a maximum error of less than 3% at both transient and steady state.